DEBT RELIEF FOR CONSUMERS − THE INTERACTION BETWEEN INSOLVENCY AND CONSUMER PROTECTION LEGISLATION (PART 1) - Melanie Roestoff; Stéfan Renke (Obiter, 2022)
In March 2002 the Department of Trade and Industry established a task team to review the legislation that has an impact on consumer credit. This resulted in a detailed report containing proposals for a new regulatory framework for consumer credit. Subsequently, in June 2005 the National Credit Bill was tabled in Parliament. Measures aimed directly at resolving over-indebtedness in the form of debt re-arrangement are introduced by the Credit Bill. The report also highlighted weaknesses in the current insolvency legislation especially with regard to available debt relief measures for consumers. It should, however, be noted that the 2000 Insolvency Bill inter alia provides for an alternative to insolvency proceedings in the form of a pre-liquidation composition. This article examines the interaction between current and proposed insolvency and consumer protection legislation with regard to debt relief measures for consumers. The question arises whether the current and the proposed debt relief measures, when introduced, will not overlap unnecessarily. Furthermore, the question whether these measures will provide adequate relief to deal with current demands is also addressed. The South African Law Reform Commission when proposing the pre-liquidation composition in the Insolvency Bill, did not indicate what its relationship should be with the administration order procedure in terms of section 74 of the Magistrates Courts’ Act. The question is therefore whether a need for administration orders will still exist if the proposed legislation relating to the pre-liquidation composition is introduced. Lastly, as South African law does not offer debt relief to debtors who have no income and no assets, proposals by the Department of Trade and Industry in the United Kingdom for a non-court based scheme of debt relief aimed at such debtors (the so-called “NINA” cases) are investigated in order to supply guidelines for South African law reform in this regard. It is submitted that the proposals in the Credit Bill on debt re-arrangement could assist debtors to manage their debt in certain circumstances. It is furthermore suggested that a combination of the proposed pre-liquidation composition and a modified administration order procedure could offer the necessary debt relief in situations where a debtor, apart from his debt in terms of a credit agreement, also has other outstanding debts. Finally, it is submitted that the “NINA” scheme could offer some guidance for the reform of South African law regarding debt relief to debtors who have no income and no assets.